Nepal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper highlights that progress on structural reforms in Nepal stalled during 1994/95 while economic performance deteriorated. Real GDP slowed as agriculture output was depressed by a less favorable monsoon, and exports declined as both the carpet and garment sectors faltered. Although the government's domestic borrowing remained low, rapid growth in private credit financed a surge in imports that in combination with weakening export demand led to a sharp reduction of the external surplus. In 1995/96, economic activity rebounded as favorable weather conditions boosted agricultural output, while inflation performance continued to be satisfactory.